Updates in the management of respiratory virus infections in ICU patients: revisiting the non-SARS-CoV-2 pathogens. Issue 12 (2nd December 2022) - Saura, Ouriel; Chommeloux, Juliette; Levy, David; Assouline, Benjamin; Lefevre, Lucie; Luyt, Charles-Edouard
ABSTRACT: Introduction: Although viruses are an underestimated cause of community-acquired pneumonias (CAP) and hospital-acquired pneumonias (HAP)/ventilator-associated pneumonias (VAP) in intensive care unit (ICU) patients, they have an impact on morbidity and mortality. Areas covered: In this perspective article, we discuss the available data regarding the management of severe influenza CAP and herpesviridae HAP/VAP. We review diagnostic and therapeutic strategies in order to give clear messages and address unsolved questions. Expert opinion: Influenza CAP affects yearly thousands of people; however, robust data regarding antiviral treatment in the most critical forms are scarce. While efficacy of oseltamivir has been investigated in randomized controlled trials (RCT) in uncomplicated influenza, only observational data are available in ICU patients. Herpesviridae are an underestimated cause of HAP/VAP in ICU patients. Whilst incidence of herpesviridae identification in samples from lower respiratory tract of ICU patients is relatively high (from 20% to 50%), efforts should be made to differentiate local reactivation from true lung infection. Only few randomized controlled trials evaluated the efficacy of antiviral treatment in herpesviridae reactivation/infection in ICU patients and all were exploratory or negative. Further studies are needed to evaluate the impact of such treatment in specific populations.